Multifunctional memantine nitrate significantly protects against glutamate-induced excitotoxicity via inhibiting calcium influx and attenuating PI3K/Akt/GSK3beta pathway. (1st July 2020) - Liu, Zheng; Qiu, Xiaoling; Mak, Shinghung; Guo, Baojian; Hu, Shengquan; Wang, Jiajun; Luo, Fangcheng; Xu, Daping; Sun, Yewei; Zhang, Gaoxiao; Cui, Guozhen; Wang, Yuqiang; et al.
Abstract: Overactivation of N -methyl-D-aspartate (NMDA) receptors has been associated with neurodegenerative disorders such as Alzheimer's disease (AD), cerebral vascular disorders and amyotrophic lateral sclerosis (ALS). We have previously designed and synthesized a series of memantine nitrate and some of them have shown vessel dilatory effects and neuroprotective effects; however, the detailed mechanisms have not been elucidated. In this study, we further demonstrated that memantine nitrate-06 (MN-06), one of the novel compounds derived from memantine, possessed significant neuroprotective effects against glutamate-induced excitotoxicity in rat primary cerebellar granule neurons (CGNs). Pretreatment of MN-06 reversed the activation of GSK3b and the suppression of phosphorylated Akt induced by glutamate. In addition, the neuroprotective effects of MN-06 could be abolished by LY294002, the specific phosphatidylinositol 3-kinase (PI3-K) inhibitor. Ca 2+ imaging shown that pretreatment of MN-06 prevented Ca 2+ influx induced by glutamate. Moreover, MN-06 might inhibit the NMDA-mediated current by antagonizing NDMA receptors, which was further confirmed by molecular docking simulation. Taken together, MN-06 protected against glutamate-induced excitotoxicity by blocking calcium influx and attenuating PI3-K/Akt/GSK-3b pathway, indicating that MN-06 might be a potential drug for treating neurodegenerative disorders. Highlights: Memantine nitrate MN-06 exhibited neuroprotective effects. MN-06 attenuated dysfunctions of PI3–K/Akt pathway induced by glutamate. MN-06 reduced Ca 2+ influx by antagonizing NMDA receptor.